Stylized facts and close dialogue: methodology in economic geography - Clark, G (Routledge, 1998)
One difference between economists and geographers is the significance attached by the former to stylized facts and the very different significance attached by the latter to the diversity of economic life. The paper begins with this distinction and argues that Krugman's theory-enslaved stylized facts may impoverish theoretical innovation in economic geography just as the efficient-markets hypothesis has had severe consequences for research in finance. An alternative to theory-enslaved stylized facts is suggested, noting the inevitable and antagonistic relationship between theory and empirical observation. My philosophical perspective is neither foundational nor postmodern, but is, rather, a version of philosophical skepticism. Having reviewed recent developments in economic geography, the claimed virtues of objectivity and the supposed dangers of subjectivity are disputed. I suggest that the former is compromised by its reliance upon a ready-made world, while the dangers of the latter are exaggerated by an implied commitment to an uncontested truth. This is the basis for arguing the virtues of close dialogue in economic geography and in the geography of finance in particular.